100 volumes of "Notes on Numerical Fluid Mechanics" : 40 years of numerical fluid mechanics and aerodynamics in retrospect - Hirschel, Ernst Heinrich; Krause, E. (Egon), 1933- (Berlin : Springer)
Includes bibliographical references